Utilization of Animal Solid Waste for Electricity Generation in the Northwest of Iran 3E Analysis for One-Year Simulation - Azher M. Abed; Holya A. Lafta; Reza Alayi; Hossein Tamim; Mohsen Sharifpur; Nima Khalilpoor; Behnam Bagheri (International Journal of Chemical Engineering)
Today, the use of renewable energy is increasing day by day. The most susceptible to renewable energy is biomass energy because it depends directly on the size of the population and does not have the problems of other renewable energies such as lack of access day and night and constant change throughout the year. For this reason, animal solid waste has been used in the research to supply electrical energy to the study area. In this regard, the amount of animal waste is considered as a source of biomass input energy. HOMER software was used to simulate the system under study. To better compare the competitiveness of this energy, photovoltaic systems and wind turbines have been used as different scenarios of electrical energy production in the study area. The results of scenario analysis showed that in all designed systems, the highest amount of energy production was in July and was related to the hottest season of the year. Among hybrid systems, the biomass system has a higher priority than other systems due to the minimum cost of energy production and total net present cost (NPC). The amount of exhaust gas from the biomass system reached 53.5 kg/yr and the biomass-wind and biomass-wind-solar systems reached 52.5 kg/yr and 52.2 kg/yr, respectively. The surplus generated electricity also increases from 2.91% to 6.65% from the biomass-wind system to the biomass-with-solar system.